Copper-doped activated carbon from amorphous cellulose for hydrogen, methane and carbon dioxide storage. (15th May 2022) - Conte, Giuseppe; Policicchio, Alfonso; De Luca, Oreste; Rudolf, Petra; Desiderio, Giovanni; Agostino, Raffaele G.
Abstract: The transition away from fossil fuel and ultimately to a carbon-neutral energy sector requires new storage materials for hydrogen and methane as well as new solutions for carbon capture and storage. Among the investigated adsorbents, activated carbons are considered especially promising because they have a high specific surface area, are lightweight, thermally and chemically stable, and easy to produce. Moreover, their porosity can be tuned and they can be produced from inexpensive and environmentally friendly raw materials. This study reports on the development and characterization of activated carbons synthesized starting from amorphous cellulose with and without the inclusion of copper nanoparticles. The aim was to investigate how the presence of different concentrations of metal nanoparticles affects porosity and gas storage properties. Therefore, the research work focused on synthesis and characterization of physical and chemical properties of pristine and metal-doped activated carbons materials and on further investigation to analyze their hydrogen, methane and carbon dioxide adsorption capacity. For an optimized Cu content the microporosity is improved, resulting in a specific surface area increase of 25%, which leads to a H2 uptake (at 77 K) higher than the theoretical value predicted by the Chahine Rule. For CH4, the storage capacity is improved by the addition of Cu but less importantly because the size of the molecule hampers easy access of the smaller pores. For CO2 a 26% increase in adsorption capacity compared to pure activated carbon was achieved, which translated with an absolute value of over 48 wt% at 298 K and 15 bar of pressure. Graphical abstract: Image 1 Highlights: Cu nanoparticles are a key factor in the development of specific surface area and porosity during the synthesis process. Textural properties worsen using over 1% of Cu nanoparticles. Microporosity improves H2 adsorption (at 77 K) more than the theoretical value predicted by the Chahine Rule. The best adsorption capacities obtained are 4 wt% for H2, 10.6 wt% for CH4 and 48.2 wt% for CO2 . High reversibility and stability of the developed material toward all gases species analyzed.